Towards a digitally fabricated disassemble-able building system: a CNC fabricated T-Slot joint - Brandão, F.; Paio, A.; Antunes, N. (eCAADe 2018 Conference, 2018)
Growing dissemination of digital fabrication technologies coupled with a renewed interest in wood as a construction material have led to a resurgence of research into integral wood joints. Recent research on digitally fabricated wood joints has focused primarily on robotic or on CNC router produced snap-fit or tab-and-slot joints. These types of joints have several problems in sheathing to structure connections. The present paper reports on research into design and fabrication of T-slot joints that allow hidden back-face connections which are disassemble-able. It is part of an ongoing research whose aim is to develop disassemble-able and mass customizable construction system of partition walls for building renovation.